1990
DOI: 10.1007/bf02010725
|View full text |Cite
|
Sign up to set email alerts
|

Ofloxacin in juvenile non-human primates and rats. Arthropathia and drug plasma concentrations

Abstract: Arthropathia in juvenile animals is the most important toxic effect induced by quinolones. We conducted pharmacokinetic and morphological studies with ofloxacin on non-human primates (Callithrix jacchus, Marmosets) and rats. In the marmoset, electron microscopy and the application of immuno-morphological methods proved to be suitable for the detection of specific alterations in cartilage (e.g. loss of proteoglycans and altered chondrocytes). Subsequently performed electron microscopic examinations in rats show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
65
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 19 publications
8
65
0
1
Order By: Relevance
“…3). These macro-and micropathological findings were in agreement with previous results of known quinolones in immature dogs [1,3,7,11], and basically resembled those reported in multiple species such as rats [4], rabbits [2], non-human primates [9] and others [5,6], although there were slight differences in the arthropathic dose among the quinolones. Unfortunately, the sensitivity of MR imaging for the detection of vesicular lesions in articular cartilage remains an unresolved issue, as Gough et al [2] reported.…”
supporting
confidence: 91%
“…3). These macro-and micropathological findings were in agreement with previous results of known quinolones in immature dogs [1,3,7,11], and basically resembled those reported in multiple species such as rats [4], rabbits [2], non-human primates [9] and others [5,6], although there were slight differences in the arthropathic dose among the quinolones. Unfortunately, the sensitivity of MR imaging for the detection of vesicular lesions in articular cartilage remains an unresolved issue, as Gough et al [2] reported.…”
supporting
confidence: 91%
“…Increase of fibronectin staining in articular cartilage has been identified as a very sensitive indicator and early reaction after quinolone treatment in immature rats and marmosets (12,25). F6rster et al (12) (23,24).…”
Section: Integrin Stainingmentioning
confidence: 99%
“…Immunohistochemical studies of articular cartilages from growing rats and marmosets dosed with ofloxacin revealed treatment-related changes in antigen expression within chondrocytes and extracellular matrix (12,25). In cartilage from marmosets that had received ofloxacin for 5 days, an increase in fibronectin staining was observed in matrix adjacent to fissures and in some areas without fissures (25). In cartilage from rats that had been dosed with ofloxacin, a similar increase of fibronectin and a reduced expression of various integrins (e.g., the fibronectin receptor avr3¡) on chondrocytes was detected (12 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…63(8): 867-872, 2001 New quinolone antimicrobial agents (quinolones) are widely used in clinical fields because of their broad spectra and bactericidal activity. However, quinolones have been reported to induce arthropathy in juvenile animals such as mice [12], rats [4, 9, 10], rabbits [11], dogs [3, 5, 8, 20], nonhuman primates [17] and others [1, 2] as a class effect of these derivatives. Among these species, the juvenile dog is thought to be most susceptible to articular cartilage lesions [6,19,20].…”
mentioning
confidence: 99%
“…However, quinolones have been reported to induce arthropathy in juvenile animals such as mice [12], rats [4,9,10], rabbits [11], dogs [3,5,8,20], nonhuman primates [17] and others [1,2] as a class effect of these derivatives. Among these species, the juvenile dog is thought to be most susceptible to articular cartilage lesions [6,19,20].…”
mentioning
confidence: 99%